Global exposure of carnivores to roads. Issue 5 (26th January 2017) - Ceia‐Hasse, Ana; Borda‐de‐Água, Luís; Grilo, Clara; Pereira, Henrique M.
Abstract: Aim: Land‐use change is a major threat to biodiversity globally. Roads cause direct mortality and limitation of individual movements, which may isolate populations and affect their viability in the long term. Here we provide the first comprehensive global assessment of the exposure of terrestrial mammalian carnivores to roads using an integrated modelling framework. Location: Global. Methods: We estimated critical road densities and critical patch sizes for each species based on a spatially explicit model and life‐history traits. We calculated the distribution of landscape fragment sizes for each carnivore species by intersecting global road density with each species range. The proportion of a species' geographical range with fragments below the critical patch size is used as an index of the vulnerability to roads. Results: We found that the carnivores expected to be most exposed to roads belong to families Felidae, Ursidae, Mustelidae, Canidae and Procyonidae. Approximately one‐third of the species most affected have not been identified by the IUCN as threatened by roads. Our model projects time to extinction that may be as low as one century for some species, such as the endangered Iberian lynx. Species are expected to be more exposed in areas with medium to high road density but, surprisingly, also in areas where road density is relatively low. Hotspots of the number of species locally endangered by roads occur in North America and Asia. Main conclusions: Our results suggest the need to reassess the status and threats of those species that have not been previously recognized as strongly affected by roads. Our framework can be applied at different spatial scales, to assess the effects of the development of the road network and inform prioritization schemes for road building, and to identify areas for conservation, and species requiring particular mitigation and restoration measures.